Incorporating Social Welfare in Program-Evaluation and Treatment Choice - Bhattacharya, Debopam; Komarova, Tatiana (The Review of Economics and Statistics, 2026)
Abstract We introduce a notion of money-metric social welfare for discrete choice under unrestricted heterogeneity and income effects. It is the maximized indirect utility under normalization of the outside option. It also equals the amount of income necessary to achieve a given level of utility, while certain choices are prohibited. We show that the distribution of this quantity is nonparametrically identified as a closed-form functional of average structural demand for the outside option, making it useful for cost-benefit analysis and optimal targeting. An illustration with private tuition subsidies in India shows that the income path of usage-maximizing subsidies differs significantly from welfare-maximizing ones.